Molecular fingerprint of high fat diet induced urinary bladder metabolic dysfunction in a rat model. - Andreas Oberbach (Public Library of Science (PLoS), 2013)
Aims/hypothesis Diabetic voiding dysfunction has been reported in epidemiological dimension of individuals with diabetes mellitus. Animal models might provide new insights into the molecular mechanisms of this dysfunction to facilitate early diagnosis and to identify new drug targets for therapeutic interventions. Methods Thirty male Sprague-Dawley rats received either chow or high-fat diet for eleven weeks. Proteomic alterations were comparatively monitored in both groups to discover a molecular fingerprinting of the urinary bladder remodelling/dysfunction. Results were validated by ELISA, Western blotting and immunohistology. Results In the proteome analysis 383 proteins were identified and canonical pathway analysis revealed a significant up-regulation of acute phase reaction, hypoxia, glycolysis, β-oxidation, and proteins related to mitochondrial dysfunction in high-fat diet rats. In contrast, calcium signalling, cytoskeletal proteins, calpain, 14-3-3η and eNOS signalling were down-regulated in this group. Interestingly, we found increased ubiquitin proteasome activity in the high-fat diet group that might explain the significant down-regulation of eNOS, 14-3-3η and calpain. Conclusions/interpretation Thus, high-fat diet is sufficient to induce significant remodelling of the urinary bladder and alterations of the molecular fingerprint. Our findings give new insights into obesity related bladder dysfunction and identified proteins that may indicate novel pathophysiological mechanisms and therefore constitute new drug targets.